PENGARUH KOMPOS JERAMI PADI TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG HIJAU (Phaseolus radiatus L) - Deno Okalia (JURNAL RISET INDRAGIRI, 2022)
This study aims to determine the effect of rice straw compost on the growth and production of mung bean (Phaseolus radiatus L). This study used a non-factorial randomized block design (RAK), namely the administration of rice straw compost (A) which consisted of 6 levels of treatment: A0 (0 g/polybag), A1 (10 g/polybag), A2 (20 g/ polybag), A3 (30 g/ polybag), A4 (40 g/ polybag), and A5 (50 g/ polybag). Based on the research that has been done, it can be concluded that the rice straw compost treatment has a significant effect on all parameters of the observation of mung bean plants, with the best results found in the A4 treatment, namely the dose of rice straw compost 40 g/polybagt with a plant height of 56.22 cm, age of emergence flower 33.00 DAT, number of pods per plant 33.82 fruit and dry seed weight per plant 26.52 grams.